Tinjauan Hukum Pelaksanaan Izin Pinjam Pakai Gor Mampis Rungan Antara Pihak Pengelola Dengan Masyarakat: Studi Di Kabupaten Sumbawa - Atika Maulina Yuniasrah; Arief Rahman (Private Law, 2022)
This research aims to find out process of lending-to-use permit of GOR Mampis Rungan Sumbawa Regency and liability of borrower party if the event of a default in the loan-to-use agreement of GOR Mampis Rungan. The method of this research is empirical legal research. The result of this research shows that the process of borrowing and using GOR Mampis Rungan, namely the prospective borrower submits a application letter for borrowing the GOR to Department of Youth, Sports and Tourism, after that it will be processed and analysis by the sport sector. If it has been approved a loan permit will be issued. If there is a default in the lending the loan-to-use agreement of GOR Mampis Rungan, Sumbawa Regency, namely in the form of compensation both material and non-material.